Establishment of a thalassaemia major quality improvement collaborative in Pakistan. Issue 5 (8th February 2019) - Hoodbhoy, Zahra; Ehsan, Lubaina; Alvi, Najveen; Sajjad, Fatimah; Asghar, Aleezay; Nadeem, Omair; Qidwai, Asim; Hussain, Shabneez; Hasan, Erum; Altaf, Sadaf; Kirmani, Salman; Hasan, Babar S
Abstract : Objectives: The aim of this study was to establish multidisciplinary care for patients with transfusion-dependent thalassaemia (TDT) by creating a TDT quality improvement (QI) collaborative in a resource-constrained setting. This study presents our initial experience of creating this collaborative, the baseline characteristics of the participants, the proposed QI interventions and the outcome metrics of the collaborative. Design and setting: TDT QI collaborative is a database comprising patients with TDT from four centres in Karachi, Pakistan. Study variables included symptoms of cardiac or endocrine dysfunction, physical examination including anthropometry and Tanner staging, chelation therapy, results of echocardiography, T2* cardiac MRI (CMR) and serum ferritin. The main outcome of this collaborative was improvement in TDT-related morbidity and mortality. Interventions addressing the key drivers of outcome were designed and implemented. Results: At the time of reporting, the total number of patients in this database was 295. Most patients reported cardiac symptoms corresponding to New York Heart Association class 2. Approximately half (52%, n=153) of the patients demonstrated severe myocardial iron overload (T2* <10 ms). Majority of the patients (58%, n=175) were not on adequate chelation therapy. There was no difference in echocardiographic measures of systolic and diastolic left ventricle among the different spectrums of iron overloaded myocardium. Conclusion: Using T2* CMR and endocrine testing, we have identified significant burden of iron siderosis in our patients with TDT. Lack of adequate iron load assessment and standardised management was observed. Interventions designed to target these key drivers of outcome are the unique part of this QI-based TDT registry.